Combining fsQCA and PLS-SEM to assess policyholders' attitude towards life settlements - Jorge de Andrés Sánchez; Laura González-Vila Puchades (European Research on Management and Business Economics (ERMBE), 2023)
Life settlements (LSs) can be considered a novel and innovative financial asset in countries where they are not yet established. This paper aims to assess the attitude (ATT) of policyholders towards participating in LSs in such countries by evaluating various variables: performance expectancy (PE), expected easiness (EE), social influence (SI), perceived ethical problems (EP), and bad feelings (BF) that may arise from this type of transaction. To achieve this goal, a questionnaire was administered to 89 individuals in Spain who possessed extensive knowledge of financial and insurance matters. The data analysis employed fuzzy set qualitative comparative analysis (fsQCA) as the basis, supplemented by partial least squares-structural equation modelling (PLS-SEM). The fsQCA results enabled the identification of policyholder profiles associated with the acceptance or rejection of LSs. Meanwhile, PLS-SEM provided insights into the net strength and statistical significance of the impact of each variable on ATT. Methodologically, this study demonstrates that fsQCA is valuable in constructing a reliable and concise framework for subsequent PLS-SEM estimation. A significant practical implication of this research is the importance of the interaction between PE and SI in the successful development of LS markets. A positive perception of financial advisors regarding these agreements emerges as a crucial factor in market growth. Moreover, the study reveals that EP and BF may significantly influence resistance towards LSs.
Keywords: A1; C3; G2; 650; Life settlementsfs; QCAPLS-SEM; Technology acceptance model